2021
DOI: 10.3389/fpsyt.2021.764738
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of Post-traumatic Stress Disorder Among Health Care Workers During the COVID-19 Pandemic: An Umbrella Review and Meta-Analysis

Abstract: Introduction: Frontline health care workers (HCWs) have had an increased risk of developing health problems during the COVID-19 pandemic. In addition to physical illness, they have experienced mental health challenges, including post-traumatic stress disorder (PTSD). The aim of this study is to investigate the prevalence of PTSD among HCWs during the COVID-19 pandemic via an umbrella review and meta-analysis.Methods: This study was conducted using the Preferred Reporting Items for Systematic Reviews and Meta-A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
46
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 61 publications
(57 citation statements)
references
References 38 publications
2
46
0
Order By: Relevance
“…Also, we found that COVID-19 traumatic stress is another factor in our five-model factor. The prevalence of post-traumatic stress disorder due to the COVID-19 pandemic is high not only to health professionals but also to the general population (Caruso et al, 2021; d’Ettorre et al, 2021; Li et al, 2021; Nagarajan et al, 2022; Sahebi et al, 2021). The prevalence of post-traumatic stress disorder during the COVID-19 pandemic reaches 15% in the general population and 21.5% in healthcare workers.…”
Section: Discussionmentioning
confidence: 99%
“…Also, we found that COVID-19 traumatic stress is another factor in our five-model factor. The prevalence of post-traumatic stress disorder due to the COVID-19 pandemic is high not only to health professionals but also to the general population (Caruso et al, 2021; d’Ettorre et al, 2021; Li et al, 2021; Nagarajan et al, 2022; Sahebi et al, 2021). The prevalence of post-traumatic stress disorder during the COVID-19 pandemic reaches 15% in the general population and 21.5% in healthcare workers.…”
Section: Discussionmentioning
confidence: 99%
“…The medical security service is very important, so the top priority is to solve the problem of PTSD prevalence of medical staff. In the previously published meta-analysis[ 22 , 23 , 24 , 25 ], the impact on the mental health of medical staff of different races during the COVID-19 pandemic was partly mentioned while not consistent. Some studies pointed out that the distribution areas were different; races were different, the mode of education and income were different, the fear of infection and the lack of confidence in the vaccine were related to the changes of mental state [ 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…The results of another meta-analysis study showed that the prevalence of PTSD after the earthquakes and floods in the children and teenager in the first, second, third and fourth 6-month period was 19.2, 30, 24.4 as well as 20.4%, respectively ( 40 ). The results of another review study showed the prevalence of PTSD among Health Care Workers during the COVID-19 was 13.52% ( 41 ). By comparing the results of the present study with the previous studies, it can be concluded that the prevalence of PTSD after the flood is high like other natural disasters and all age groups are at risk of mental disorders after the flood, especially PTSD.…”
Section: Discussionmentioning
confidence: 99%